2016
DOI: 10.1002/mop.29623
|View full text |Cite
|
Sign up to set email alerts
|

A 1 × 2 triple‐band printed antenna array for use in next generation flying AD‐HOC networks (FANETs)

Abstract: A triple‐band 1 x 2 microstrip patch antenna array is proposed for use in next generation flying ad‐hoc network (FANET) communication in multi‐UAV systems. The antenna array resonates in the 3.6 GHz, 5.2 GHz and 6.7 GHz frequency bands, respectively. The antenna was designed and simulated using Agilent ADS Momentum using FR4 epoxy glass substrate (εr = 4.2 and h = 1.66mm). A hybrid feed technique is used for antenna arrays with quarter‐wave transformer based network to match the impedance from the feed‐point t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Thus, leading to a large amount of routing overhead that causes information loss. [25][26][27][28][29][30] are some of the authors that concentrated on improving the communication models in FANET. Muhammad et al, [25] and Antinio et al, [26] developed a hybrid communication scheme for the efficient and low-cost deployment of future FANET and a new domain for communications in FANET respectively.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, leading to a large amount of routing overhead that causes information loss. [25][26][27][28][29][30] are some of the authors that concentrated on improving the communication models in FANET. Muhammad et al, [25] and Antinio et al, [26] developed a hybrid communication scheme for the efficient and low-cost deployment of future FANET and a new domain for communications in FANET respectively.…”
Section: Related Workmentioning
confidence: 99%
“…The communication strength between two nodes is dependent on the distance between them. Following other academic [29] and industrial [30] papers, normalized transmission rates and ranges are adopted in this work. With application to sports coverage, we adopted a football field scenario of 160 feet (48.5m) wide and 360 feet (109.1m) long.…”
Section: Basic Assumption and Problem Inputmentioning
confidence: 99%
“…It is also suggested that longer transmission ranges can be achieved with the help of directional antenna as compare to omni‐directional antenna and spatial rescue of network significantly increases with the help of directional MAC protocols . In the past, researchers have proposed multiple antenna designs and also suggested their implementation techniques for different type of UAVs. Current small UAVs are prototyped with commercial‐of‐the‐shelf (COTS) equipment which may consists of Zigbee radio modules along with the monopole antenna for communication purposes .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, researchers have proposed multiple antenna designs and also suggested their implementation techniques for different type of UAVs. Current small UAVs are prototyped with commercial‐of‐the‐shelf (COTS) equipment which may consists of Zigbee radio modules along with the monopole antenna for communication purposes . Recent research suggested the use of embedded antennas to enhance the UAV‐to‐UAV (U2U) and UAV‐to‐ground (U2G) communications.…”
Section: Introductionmentioning
confidence: 99%
“…In a design, a dual-excitation approach with dumbbell-shaped defected ground structure (DGS) was used for reconfigurability in beam steering, and improvement in front to back-lobe ratio (FBR) [4,5]. To avoid the problem of narrow bandwidth a coplanar waveguide (CPW) was used for designing CP polarized rhombic antennas for radio receivers [6].…”
Section: Introductionmentioning
confidence: 99%